2018
DOI: 10.1177/2325967117747275
|View full text |Cite
|
Sign up to set email alerts
|

Preseason Adductor Squeeze Strength in 303 Spanish Male Soccer Athletes: A Cross-sectional Study

Abstract: Background:Hip adductor muscle weakness and a history of groin injury both have been identified as strong risk factors for sustaining a new groin injury. Current groin pain and age have been associated with hip adductor strength. These factors could be related, but this has never been investigated.Purpose:To investigate whether soccer athletes with past-season groin pain and with different durations of past-season groin pain had lower preseason hip adductor squeeze strength compared with those without past-sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 30 publications
2
29
0
2
Order By: Relevance
“…The reporting of this prospective cohort study adhered to the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) guidelines . We obtained the present data from a larger study that investigates groin and hamstring injuries in male football . Local ethics committee ( Consell Catala de l'Esport ) approval was received before the study began (reference number 08/2015/CEICEGC).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reporting of this prospective cohort study adhered to the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) guidelines . We obtained the present data from a larger study that investigates groin and hamstring injuries in male football . Local ethics committee ( Consell Catala de l'Esport ) approval was received before the study began (reference number 08/2015/CEICEGC).…”
Section: Methodsmentioning
confidence: 99%
“…14 We obtained the present data from a larger study that investigates groin and hamstring injuries in male football. 15 Local ethics committee (Consell Catala de l'Esport) approval was received before the study began (reference number 08/2015/CEICEGC). The study protocol was in accordance with the Helsinki Declaration.…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…Several non-modifiable internal risk factors such as previous injury (Engebretsen, Myklebust, Holme, & Engebretsen, 2010;Mosler et al, 2018b), older age (Arnason et al, 2004;O'Connor, 2004), higher level of competition (Tyler, Nicholas, Campbell, & McHugh, 2001), and modifiable risk factors such as decreased range of hip abduction and internal rotation motion (Arnason et al, 2004;Ibrahim, Murrell, & Knapman, 2007;Tak et al, 2016) have been related to an increased likelihood of suffering a groin injury in football players. In addition, isometric adductor muscle weakness and/or a lower ratio between adductor/abductor muscle strength have also been reported as possible physical risk factors for groin injury in football (Engebretsen, Myklebust, Holme, Engebretsen, & Bahr, 2010;Esteve et al, 2018) and other sports (Tyler et al, 2001;Crow et al, 2010;Ryan, DeBurca, & Mc Creesh, 2014;Moreno-P erez, Lopez-Valenciano, Barbado, Moreside, Elvira J, & Vera-Garcia, 2017). The combination of adductor muscle weakness and previous groin injury could further increase the probability of developing groin pain (Engebretsen et al, 2010;Esteve et al, 2018;Mosler et al, 2018b).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, isometric adductor muscle weakness and/or a lower ratio between adductor/abductor muscle strength have also been reported as possible physical risk factors for groin injury in football (Engebretsen, Myklebust, Holme, Engebretsen, & Bahr, 2010;Esteve et al, 2018) and other sports (Tyler et al, 2001;Crow et al, 2010;Ryan, DeBurca, & Mc Creesh, 2014;Moreno-P erez, Lopez-Valenciano, Barbado, Moreside, Elvira J, & Vera-Garcia, 2017). The combination of adductor muscle weakness and previous groin injury could further increase the probability of developing groin pain (Engebretsen et al, 2010;Esteve et al, 2018;Mosler et al, 2018b). Esteve et al (2018) in a cross-sectional study of amateur football players identified that players who suffered from past-season groin pain for more than 6 weeks showed 13%e19% lower isometric adductor strength than the control players.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation